Nuclear accumulation of symplekin promotes cellular proliferation and dedifferentiation in an ERK1/2-dependent manner - Chen Zhang (Nature Portfolio, 2017)
Abstract Symplekin is a multifunctional protein that localizes to both tight junctions and the nucleus in polarized epithelial cells, with confirmed roles in mRNA maturation, transcriptional modulation and tight-junction assembly. However, the mechanisms governing its subcellular distribution and related functions remain unclear. In this study, we found that symplekin primarily localizes to the nuclei of cultured dedifferentiated colorectal cancer cells, and nuclear symplekin showed higher phosphorylation and binding affinity with YBX3 than its membrane fraction. Moreover, the accumulation of nuclear symplekin promoted cell proliferation and dedifferentiation as well as β-catenin transactivation in vitro. Nuclear symplekin acts as a transcriptional co-activator for the expression of many cell cycle-related genes. Furthermore, extracellular signal-regulated kinase (ERK) phosphorylated symplekin at T1257 to facilitate its nuclear accumulation upon epidermal growth factor (EGF) stimulation. Meanwhile, reduction of total symplekin also induced certain epithelial-mesenchymal transition features in HT-29 cells. Taken together, our results confirm the coordinated roles of symplekin in cell junctions and gene transcription, which are related to its subcellular localization. The significance of nuclear symplekin in tumorigenesis is also highlighted, and ERK-dependent phosphorylation represents a mechanism for its subcellular sorting.